Switch to aflibercept or ranibizumab after initial treatment with bevacizumab in eyes with neovascular AMD - Maria Waizel (BMC Ophthalmology, 2017)
Abstract Background To evaluate changes in central macular thickness (CMT) and visual outcome in patients with neovascular age-related macular degeneration (AMD) treated initially with bevacizumab and subsequently switched to either aflibercept or ranibizumab. Methods Observational clinical study was performed. We measured the structural outcome (CMT on SD-OCT; μm) and the visual outcome (best corrected visual acuity (BCVA); logMAR), as follows: before treatment (at baseline), following bevacizumab treatment (switch follow-up) and after switching from bevacizumab to aflibercept- or ranibizumab treatment (final follow-up, AG/, RG). Results From a total of 96 eyes treated with intravitreal injections of bevacizumab (10.5 ± 7.6 (mean ± SD)), 58 eyes switched to aflibercept (6.5 ± 3.9; AG) and 38 eyes switched to ranibizumab (7.1 ± 5.3; RG) (≥ 3 injections, each). In addition, these eyes were compared to 37 eyes under bevacizumab monotherapy. Primary outcome: In the AG, the CMT decreased slightly from 430 ± 220 μm at baseline to 419 ± 212 μm at switch follow-up (p = 0.86), but decreased significantly to 318 ± 159 μm at final follow-up, AG (p < 0.0001). In the ranibizumab group (RG), the CMT increased from 396 ± 174 μm at baseline to 499 ± 333 μm at switch follow-up (p = 0.012), but decreased significantly to 394 ± 202 μm at final follow-up, RG (p = 0.007). Secondary outcome: In the AG, the mean BCVA worsened from logMAR 0.57 ± 0.33 at baseline to 0.63 ± 0.30 at switch follow-up and improved slightly to 0.53 ± 0.71 at final follow-up, AG (p = 0.46). In the RG, mean BCVA worsened from 0.57 ± 0.28 at baseline to 0.64 ± 0.31 at switch follow-up and improved slightly to 0.60 ± 0.36 at final follow-up, RG (p = 0.64). Conclusion Switching from bevacizumab to either aflibercept, or ranibizumab, has a strong anatomical effect in eyes with neovascular AMD. Nevertheless, even if the switch to aflibercept shows a minimal functional benefit over that to ranibizumab, visual prognosis remains limited.